Bulbophyllum deergongense (Dendrobiinae; Malaxideae; Epidendroideae; Orchidaceae), a new species from Tibet, China - Miao, Jiang-Lin; Zhang, Hua-Yuan; Zhu, Wen-Tao; Liu, Zhen; Ji, Hong-Yu; Liu, Zhong-Jian; Zhai, Jun-Wen (Phytotaxa, 2023)
A new species of Orchidaceae, Bulbophyllum deergongense, is described from Motuo (Tibet, China) based on morphological traits and molecular phylogenetic analysis. This new species is similar to B. reptans but differs in its elongate cylindrical pseudobulbs with prominent ridges, yellowish-green flower without markings, and oblong-ovoid petal with a round apical purple-brown spot. Molecular phylogenetic analyses based on two plastid makers (matK and psbA-trnH) and two nuclear DNA (ITS and Xdh) support B. deergongense as a new species of B. section Reptantia, in which it is sister to B. reptans.